¿Hay que constitucionalizar la lucha contra el terrorismo? (2016)
The permanence of a high terrorist threat to Western democracies, evidenced primarilywith the weakening of the protection of fundamental rights since the attacksof September 11, 2001, invites the Rule of Law, in the context of the means andguarantees, to fight against terrorism. In this regard, it is relevant to ask whetherthe inclusion in the Constitution of stipulations in the fight against terrorism is tofulfill the challenges democracies are facing. From an analysis of comparative law,this study aims to establish the terms of the debate, taking into account the strengthsand limitations of the constitutionalization process of the fight against terrorism.